CROSS-SECTIONAL STUDY ON THE LEVEL OF KNOWLEDGE ON THE USE OF DISINFECTANTS IN MEDICAL PRACTICE - Catalina Iulia Saveanu; Georgiana Damian; Bianca Toader; Irina Bamboi; Livia Ionela Bobu; Alexandra Ecaterina Saveanu; Petru Daniel Cioloca; Dana Anistoroaei (Romanian Journal of Oral Rehabilitation)
Introduction: Disinfectants play an essential role in dental practice, contributing to the prevention of infection transmission and the safety of medical procedures. In Romania, their use is regulated by the Ministry of Health, according to European standards regarding efficiency and spectrum of action. Aim of the study: The purpose of this study was to assess the level of knowledge and attitudes of medical personnel towards the use of disinfectants, as well as to analyse the degree of compliance with international infection control protocols. Materials and methods: The cross-sectional study was conducted between October 2023 and March 2024 and included 214 subjects with active practice in Iasi, who completed an online questionnaire. Results: Average level of knowledge regarding the types of disinfectants used in the office, with significant differences depending on the length of service in the profession. Conclusions: Physician with over 10 years of experience demonstrated a higher level of knowledge compared to those at the beginning of their careers. The study's conclusion emphasizes the need to intensify ongoing education on the correct use of disinfectants, given their role in reducing the risk of contamination in the medical environment.